An ambipolar transistor based on a monolayer WS2 using lithium ions injection - Heshen Wang; Qiye Liu; Xuemeng Feng; Zhan Zhang; Kai Wang; Zhaojun Liu; Jun-Feng Dai (Materials Research Express, 2020)
Ambipolar field-effect transistor (FET) devices based on two-dimensional (2D) materials have been attracted much attention due to potential applications in integrated circuits, flexible electronics and optical sensors. However, it is difficult to tune Fermi level between conduction and valence bands using a traditional SiO _2 as dielectric layer. Here, we employed the lithium-ion conductive glass ceramic (LICGC) as the back-gate electrode in a monolayer WS _2 FET. The effective accumulation and dissipation of Li ^+ ions in the interface induce a wide tune of Fermi level in the conducting channel by electron and hole doping, which show an ambipolar transport characteristics with threshold voltages at 0.9 V and −1.3 V, respectively. Our results provide an opportunity for fabricating ultra-thin ambipolar FET based on 2D materials.